The Socio-economic Effects of Oil Royalties in Casanare state, period 2004 – 2015 - Pava Vargas, Andrés Fernando; Lemos Valencia, Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Although the remarkable oil exploitation has allowed Casanare state to receive significant income as royalties, the socio-economic structure reached in it has not been as expected. Therefore, the purpose of thisdocument is to demonstrate that the management and administration applied to these resources (represented by the Institutional Quality Index) was not consistent with the socio-economic effects achievedin this state, during the period 2004-2015. This demonstration, which gave rise, at the same time, to a relationship with the so-called natural resources curse for this region, was defined after analyzing the resultsobtained with the estimated linear regressions, through the ordinary least squares method, and its comparisons, with the results of the other highlighted states in oil production, under the criteria of the Ragin’s similarity and difference method.